Comparing motivations for community participation in Orange Farm and Sandton - Padiachee, Mickey Viesna (My University, 1997)
Legislation provided the broad framework for participation. The constitutional mandate of local government is to ensure basic service is delivered to the people. To achieve this, local government is obligated to involve communities in its attempts at local governance. The framework for participation was laid, but the vehicles for participation were clearly defined. The community has different reasons for participating. The different levels of participation were highlighted. The concept of governance, as opposed to government, was also defined in the research in an attempt to find a clearer definition of participation. The research also provided insight into the difference between consultation, participation and effective participation. The research outlines the difference between consultation, participation and effective participation. It was confirmed that a partnership between government and civil society needs to be established in order to achieve the broad developmental objectives of both the community and government.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfilment of requirements for the degree of Master of Management
Keywords: Local government -- South Africa -- Citizen participation.; Community development -- South Africa.